SERVICE QUALITY OF INDIAN BANKS: A FUZZY INFERENCE SYSTEM APPROACH - Sreekumar; Sabita Mahapatra; S. S. Mahapatra (Asian Academy of Management Journal, 2015)
A major shift has been observed in the banking sector in recent times worldwide. The Indian banking sector has witnessed a massive transformation over the last few years due to the introduction of certain government policies. Banks are now considering the development of new service quality policies and strategies that promote customer satisfaction and loyalty. The present study attempts to evaluate the service quality of Indian banks from the customer’s perspective. We propose a fuzzy inference system for predicting various dimensions of service and identifying deficient service dimensions that promote effective strategy design.